Epidural stimulation with locomotor training ameliorates unstable blood pressure after tetraplegia. A case report. Issue 2 (23rd January 2022) - Gorgey, Ashraf S.; Sutor, Tommy W.; Goldsmith, Jacob A.; Ennasr, Areej N.; Lavis, Timothy D.; Cifu, David X.; Trainer, Robert
Abstract: A male with C7 complete tetraplegia participated in 14 weeks of body weight supported treadmill training (BWSTT) combined with spinal cord epidural stimulation (SCES), 4 weeks of no intervention, and two more weeks of BWSTT + SCES. The participant presented with unstable resting seated blood pressure (BP; 131/66 mmHg). After retrospective analysis, resting systolic BP decreased and diastolic BP increased, yielding a safe mean arterial BP. There was a fivefold increase in BWSTT bouts per session, and percentage of body weight support decreased to 69%. BWSTT + SCES safely and effectively regulated resting BP and mitigated symptoms of orthostatic intolerance. These effects were not maintained after 4 weeks without training.